The Transition of The Central Port of Colonial Era : From Old Bataviato Tanjung Priok Port - Ahmad Fauzan Baihaqi; Zakiya Darojat (Insaniyat : Journal of Islam and Humanities, 2018)
This paper discusses the ports and government policy particularly in the transition of the central port of colonial period of the old port of Batavia to the port of Tanjung Priok Year 1887-1930. The aim of this research is to understand the colonial response to the development of international shipping world, which impact on the colonial economy. Here, the position of the Dutch East Indies must dare to take the policy to change the trading center is no longer in the Port near the old city but must move to the east of Batavia namely Tanjung Priok.The method used in this research is qualitative. While the data collection is done through literature research and documentation. This data analysis technique based on heuristic techniques, verification, interpretation, and historiography. Based on the research conducted, it is found that the removal of port from the old town of Batavia to Tanjung Priok which allegedly the Dutch East Indies economic actors will not grow because of the rarity of people living around the harbor. The facts in the field of Tanjung Priok developed into the largest international port in the territory of the Indies Netherlands.The results show that the development of the harbor east of Batavia is at the center of the old city portographic port of Batavia which has high sedimentation of large ships unable to dock to the port. The Tanjung Priok central port is growing on the basis of a colonial annual report of the vast number of outposts with 20 other countries that have their homecoming in the Port.